2019
DOI: 10.1039/c9ra00082h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solvents on the DACBO-catalyzed vinylogous Henry reaction of isatin with 3,5-dimethyl-4-nitroisoxazole “on-water” and in solution from QM/MM MC simulations

Abstract: QM/MM MC simulations indicate that the special hydrogen bonding effects are the main source of the rate enhancement of the title reaction on water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Quantum mechanics/molecular mechanics (QM/MM) approaches are often used to understand catalyst-free Type III reactions, and a few examples of organocatalytic reactions have been reported. 56 The difficulty of calculating catalytic reactions lies in the fact that the structural fluctuation of a catalyst and its surroundings in aqueous environments, because of hydration, significantly multiplies the number of transition states en route to the desired product. Although the artificial force-induced reaction (AFIR) method enabled the challenging systematic sampling of transition states to determine the stereochemical information on the reactions performed in aqueous media, 57 there has been no QM study on catalytically accelerated Type III reactions at the interface.…”
Section: New Frontiers and Challenges In Synthetic Organic “Aquachemistry”mentioning
confidence: 99%
“…Quantum mechanics/molecular mechanics (QM/MM) approaches are often used to understand catalyst-free Type III reactions, and a few examples of organocatalytic reactions have been reported. 56 The difficulty of calculating catalytic reactions lies in the fact that the structural fluctuation of a catalyst and its surroundings in aqueous environments, because of hydration, significantly multiplies the number of transition states en route to the desired product. Although the artificial force-induced reaction (AFIR) method enabled the challenging systematic sampling of transition states to determine the stereochemical information on the reactions performed in aqueous media, 57 there has been no QM study on catalytically accelerated Type III reactions at the interface.…”
Section: New Frontiers and Challenges In Synthetic Organic “Aquachemistry”mentioning
confidence: 99%
“…Zhang et al first reported the vinylogous, henry reaction between isatin and 3,5-dialkyl-4-nitroisoxazole, leading to isoxazolesubstituted 3-hydroxy-2-oxindole derivatives, medicinally important compounds [20], also provided the basis for removal of industrial dye wastewater [21]. In this study, we discuss with detail "Synthesis of isatin and its derivatives and their applications in biological system" because isatin play a key effects like ascorbic acid, hydroxyl amino acids, omeprazole, thiol compounds and imidazole etc.…”
Section: -P-(p-(alkoxycarbonyl) Phenyl) Carbamoyl) Phenyl)mentioning
confidence: 99%
“…A lot of effort has been undertaken to computationally describe and understand the selectivity of organic reactions. Reactions already studied in literature include the Wittig reaction [ 35 ], organocatalytic addition to , -unsaturated ketones [ 36 ], chiral catalyzed ketimine-ene reactions [ 37 ], weak acid dissociation [ 38 ], organocatalytic S 2 reactions [ 39 , 40 ], the catalytic vinylogous Henry reaction [ 41 ], base-catalyzed Knoevenagel condensations [ 42 , 43 ], the Meyer–Schuster rearrangement [ 44 ], enantiomerization of axially chiral biphenyls [ 45 ], and also proline-catalyzed reactions [ 46 , 47 , 48 ]. While some of these studies obtained their results by using static quantum chemical calculations and frequently described solvent influence via continuum solvation models [ 37 , 39 , 40 , 42 , 43 , 44 , 49 , 50 , 51 ], others were based on molecular dynamics simulations and often used tools such as metadynamics [ 35 , 38 , 43 , 46 , 52 , 53 , 54 ] and umbrella sampling [ 45 ] to investigate the potential energy surfaces of the reactions.…”
Section: Introductionmentioning
confidence: 99%